1986
DOI: 10.1051/rnd:19860101
|View full text |Cite
|
Sign up to set email alerts
|

Milking lactating mares using oxytocin : milk volume and composition

Abstract: Summary. Ten

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…The obtained milk volumes per milking after correction for body weight were lower than those of naturally lactating mares [9], but were comparable with those of mares with induced lactation [2]. A previous report suggested that a mare with induced lactation was ready for adoption when milk production reached 3 to 5 l per day for a 500-kg horse [4].…”
Section: Discussionmentioning
confidence: 99%
“…The obtained milk volumes per milking after correction for body weight were lower than those of naturally lactating mares [9], but were comparable with those of mares with induced lactation [2]. A previous report suggested that a mare with induced lactation was ready for adoption when milk production reached 3 to 5 l per day for a 500-kg horse [4].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of milking (Doreau et al 1986a) showed that reproducibility of fat content was low from one milking to another. This may explain why lactose and N contents were less variable, except for colostrum N, as noted by Johnston et al (1970) and by Balbierz et al (1975).…”
Section: Individual Differencesmentioning
confidence: 96%
“…Mares were milked manually using a technique of mare-foal separation and oxytocin injection, according to the method of Doreau et al (1986a). Each milking represented the amount secreted during the mean time between two sucklings, depending on lactation stage, as determined in studies of nursing behaviour (MartinRosset et al 1978): 30, 40, 60 and 90 min for colostrum and milks from weeks 1, 4 and 8 respectively.…”
Section: Measurementsmentioning
confidence: 99%